Electro polymerization for (N-Terminal tetrahydrophthalamic acid) for Anti-corrosion and Biological Activity Applications - Saleh, Khulood A.; Ali, Mayasa I. (Iraqi Journal of Science, 2020)
The present work reports the electrochemical synthesis of poly N Terminal tetrahydrophthalamic acid on stainless steel 316 (S.S), which acts as a working electrode, using an electrochemical polymerization technique. Fourier Transform Infrared Spectroscopy (FT-IR), Atomic Force Microscope (AFM) and Scanning Electron Microscope (SEM) characterized the formed polymer film. Corrosion protection tests for coated and uncoated S.S with polymer film were studied in 0.2 M hydrochloric acid (HCl) solution by using electrochemical polarization technique. Kinetic and thermodynamic activation parameters (Ea, A, Î”H*, Î”S* and Î”G*) were calculated. The biological activity of the polymeric film was determined against Gram positive (Staphylococcus aureus; Staph.aure) and negative bacteria (Escherichia coli; E.coli).In addition, the polymer film was modified with nanomaterials(ZnOnnano and Graphene).